Immune-responsive gene 1 (IRG1) and dimethyl itaconate are involved in the mussel immune response. Issue 106 (November 2020) - Sendra, M.; Saco, A.; Rey-Campos, M.; Novoa, B.; Figueras, A.
Abstract: Immune-responsive gene 1 ( irg1 ) is a gene that is well-conserved among different taxa and is highly expressed in the mussel Mytilus galloprovincialis at the constitutive level. The expression of this gene increases after a bacterial infection, primarily in haemocytes. irg1 catalyses the production of itaconic acid from cis-aconitic acid in the Krebs cycle. Recently, itaconate has been revealed as an immune metabolite involved in macrophage polarization. In this work, we studied the effects of exogenous dimethyl itaconate (DI) on mussels in vitro and in vivo at relevant previously described endogenous concentrations and in mussels infected with Vibrio splendidus . DI did not have adverse effects on the haemocytes viability, apoptotic cells, proliferation and phagocytic activity; however, haemocyte size, velocity and accumulated distance were decreased. The antibacterial activity of DI in vitro and in vivo was observed with high concentrations of DI, that is, 30 and 50 mM, respectively. Furthermore, DI inhibited total ROS, increased mitochondrial ROS and modulated antioxidant genes, such as SOD and CAT, related to Nrf2 activation. In this research, we have demonstrated some important pathways in haemocytes in which itaconate can be involved after its production in a bacterial infection. Highlights: A conserved role of irg1 against bacterial infections was elucidated in mussels. The antibacterial activity of DI was demonstrated in haemocytes exposed to V. splendidus. DI did not affect the functionality of haemocytes, but their motility was decreased. DI inhibited basal ROS and zymosan-mediated respiratory burst but increased mitochondrial ROS. DI stimulated Nrf2 activation, with CAT and SOD antioxidative genes being upregulated.